The criminalisation of cartels in South Africa, United States and Australia and the effects of the Corporate Leniency Policy - Rowan, Tamsyn (Department of Commercial Law, 2020)
With the recent changes to the Competition Act1 , specifically with the inclusion of Section 73A2 which came into effect on the 1 May 2017 the amendment now makes provision for cartelists to face criminal charges for infringing Section 43 of the Act. Section 44 disallows firms from engaging cartel conduct and the objective of the recent amendment is to promote consumer welfare as well as to break the barriers to entry. Furthermore, allow for an open market and to promote the inclusion of all whom live in South Africa. To prohibit those involved in 'fixing of purchase' and or 'selling prices, dividing markets and/or involved collusive tendering amongst firms'. Despite the criminal sanctions created to deter cartels, firms or directors still are involved in collusive conduct. Cartel activity could not only be damaging to a firms' or directors' reputation, but also results in significant financial losses. With the recent implementation of S73A5 there is a more stern approach followed by our legislature by now holding directors of firms criminally liable for collusive conduct. What this paper seeks to address is the question as to whether the new developments made by the legislature allows for proper implementation in South Africa. Moreover, if the National Prosecuting Authority as the authoritative body has the competency to fully deal with the complexity of cartels. The South African model will be carefully examined against the backdrop of the United States and Australian advanced antitrust laws. Equally, as important also looking at what makes the United States and Australia more effective in their cartel detection and prevention. Particular attention will be given to the leniency policy which plays a pivotal role in prohibiting cartel conduct. And how criminal and civil sanctions should be considered in conjunction with leniency in an attempt to deter and eliminate cartel conduct.